Bathymetry of Reykjanes Ridge: A methodological approach - Banul, Karolina, 1987- (2014)
The sea floor is one of the Earths parts that still are mostly unexplored. Recent multibeam technology has now opened up new opportunities to increase our knowledge in this hitherto hidden part of the world. In this study part of the Reykjanes Ridge was analysed in order to create a high resolution and comprehensive topographic map of this northern part of the Mid-Atlantic Ocean Ridge. The general aims of the study were to i) develop seamless method from Caris, a raw analytical program for multibeam data, to ArcInfo, a spatial analytical program of geographical data; ii) to assess and modify multibeam datasets from different time periods (1994, 2006, 2007 and 2013); and iii) to conduct time-separated comparison analysis of morphological structures of the sea floor, and in that way assess potential submarine volcanic activity through time. High-resolution model of the spreading oceanic crust was created using data from precise multibeam echo-sounders. Based on the mapped topography volcanic structures were identified and analysed. Time-separated change detection analysis was further conducted using both quantitative raster based method and qualitative visual assessment. The results of the comparison analysis do reveal evidence about changes in topography of the Reykjanes Ridge. Thus, for the first time an area of the ridge has been identified as a potential eruption and/or volcano-tectonic site between 1994 and 2013.The resulting high resolution mapping furthermore add valuable knowledge as regard the Reykjanes Ridge morphology and subsequently the Mid-Atlantic Ocean Ridge, and moreover opens possibilities for further geographical and geological interpretations of submarine volcanic and tectonic processes along the Ocean Ridge. Key words: Sea floor morphology, multibeam data, GIS, Reykjanes Ridge, Iceland Erasmus Mundus GEM programmme